Pengaruh Pelayanan Teller terhadap Tingkat Kepuasan Nasabah pada Bank Syariah Indonesia Kantor Cabang Pembantu Stabat Proklamasi - Nurlatifah Manurung; Khairina Tambunan (Medan Resource Center, 2021)
This study is situated within the growing competition among Islamic banks, where service quality—particularly teller performance—has become a strategic determinant of customer satisfaction at Bank Syariah Indonesia, Kantor Cabang Pembantu Stabat Proklamasi. It addresses the central question of whether teller services significantly influence customer satisfaction by employing an analytical quantitative design with a sample of thirty-six customers selected from the bank’s client population. Teller service was treated as the independent variable and customer satisfaction as the dependent variable, with data analyzed through validity and reliability tests, normality testing, simple regression, t-tests, and correlation analysis using Microsoft Excel 2007 and Statistical Package for the Social Sciences version 22.0. The results demonstrate a statistically significant positive effect of teller services on customer satisfaction, with an effect size of 0.651, indicating that approximately 56.1 percent of the variation in customer satisfaction is explained by teller service performance. The remaining variance is attributable to factors outside the regression model. The study argues that strengthening teller professionalism and service responsiveness constitutes a critical pathway for enhancing customer satisfaction and sustaining institutional competitiveness in Islamic banking.